Graphene oxide‐ellagic acid nanocomposite as effective anticancer and antimicrobial agent - Samer Hasan Hussein‐Al‐Ali; Suha Mujahed Abudoleh; Mohd Zobir Hussein; Saifullah Bullo; Arul Palanisamy (IET Nanobiotechnology)
Abstract In this study, ellagic acid (ELA), a skin anticancer drug, is capped on the surface(s) of functionalised graphene oxide (GO) nano‐sheets through electrostatic and π–π staking interactions. The prepared ELA‐GO nanocomposite have been thoroughly characterised by using eight techniques: Fourier‐transform infrared spectroscopy (FTIR), zeta potential, X‐ray diffraction (XRD), thermogravimetric analysis (TGA), Raman spectroscopy, atomic force microscopy (AFM) topographic imaging, transmission electron microscopy (TEM), and surface morphology via scanning electron microscopy (SEM). Furthermore, ELA drug loading and release behaviours from ELA‐GO nanocomposite were studied. The ELA‐GO nanocomposite has a uniform size distribution averaging 88 nm and high drug loading capacity of 30 wt.%. The in vitro drug release behaviour of ELA from the nanocomposite was investigated by UV–Vis spectrometry at a wavelength of λmax 257 nm. The data confirmed prolonged ELA release over 5000 min at physiological pH (7.4). Finally, the IC50 of this ELA‐GO nanocomposite was found to be 6.16 µg/ml against B16 cell line; ELA and GO did not show any cytotoxic effects up to 50 µg/ml on the same cell lines.